Integration of prevention and care of sexually transmitted infections with family planning services: what is the evidence for public health benefits? - K.L. Dehne; R. Snow; K.R. O'Reilly
It has been widely believed that, by combining the services for preventing and treating sexually transmitted infections (STI) with those for family planning (FP), STI coverage would increase and the combined service would be of higher quality and more responsive to the needs of women. So far, there is little concrete evidence that integration has had such an impact. Besides the absence of documentation, a clear definition of integration is lacking. We therefore carried out a comprehensive review of concrete experiences with integrated services, and present a summary of our findings in this article. The results indicate that the tasks of STI prevention, such as education for risk reduction and counselling, have been integrated into family planning services much more frequently than the tasks of STI diagnosis and treatment. Some STI/FP integration efforts appear to have been beneficial, for instance when the integration of STI/HIV prevention had a positive impact on client satisfaction, and on the acceptance of family planning. Less clear is whether STI prevention, when concentrated among traditional FP clients, is having a positive impact on STI risk behaviours or condom use. A few projects have reported increases in STI caseloads following integration. In some projects, FP providers were trained in STI case management, but few clients were subsequently treated.